2022
DOI: 10.3390/ijms23084242
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Traits and Functional Exploration of BES1 Gene Family in Plants

Abstract: The BES1 (BRI1-EMSSUPPRESSOR1) gene family is a unique class of transcription factors that play dynamic roles in the Brassinosteroids (BRs) signaling pathway. The published genome sequences of a large number of plants provide an opportunity to identify and perform a comprehensive functional study on the BES1 gene family for their potential roles in developmental processes and stress responses. A total of 135 BES1 genes in 27 plant species were recognized and characterized, which were divided into five well-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The overexpression of OsBES1-3 and OsBES1-5 in rice increased the root growth of transgenic lines under drought stress, and transgenic Arabidopsis lines with overexpressed cotton GhBES1-4 showed salt tolerance [51]. The overexpression of PtrBES1-7 in Populus trichocarpa enhanced tolerance to drought stress by improving the ability to scavenge reactive oxygen species and antioxidant enzymes superoxide dismutase and peroxidase [54,55]. Previous studies showed that BES1 genes were induced by different abiotic stresses such as drought, heat, salinity, cold and ABA [56].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of OsBES1-3 and OsBES1-5 in rice increased the root growth of transgenic lines under drought stress, and transgenic Arabidopsis lines with overexpressed cotton GhBES1-4 showed salt tolerance [51]. The overexpression of PtrBES1-7 in Populus trichocarpa enhanced tolerance to drought stress by improving the ability to scavenge reactive oxygen species and antioxidant enzymes superoxide dismutase and peroxidase [54,55]. Previous studies showed that BES1 genes were induced by different abiotic stresses such as drought, heat, salinity, cold and ABA [56].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by He et al [91] revealed that OsPIP1 encoding aquaporin interacts with other proteins to promote water uptake and seed germination. Furthermore, BES1/BZR1, a family of Brassinosteroids transcriptional regulators, were recently proposed to regulate plant development [92], kernel size in rice [50] and maize [51] through interaction with several proteins [93].…”
Section: The Qgl1-1 Bfsg Qtl Harbors Genes Involved In Post-embryonic...mentioning
confidence: 99%
“…A study conducted by He, et al [91] revealed that OsPIP1 encoding aquaporin interacts with other proteins to promote water uptake and seed germination. Furthermore, BES1/BZR1, a family of Brassinosteroids transcriptional regulator, were recently proposed to regulate plant development [92], kernel size in rice [50] and maize [51] through interaction with several proteins [93].…”
Section: The Grain Width Thickness and Lwr-associated Qtls Qgw1-1 Bsf...mentioning
confidence: 99%